Children and money : cultural developmental psychology of pocket money - Takahashi, Noboru, 1959-; Yamamoto, Toshiya (Social psychologist), 1959- (Perspectives on human development., 2020)
"In the "Pocket Money Project," researchers from four countries, Japan, Korea, China, and Vietnam collaborated and studied how children in those four countries were involved with money, combining various research methods and approaches. What our project tries to present throughout this book is that money is not only just a tool of exchange in the context of the market economy; but, it also serves as a tool to mediate human relationships in individual cultures; and the tool is used and mediated by norms. The structure of the norms differs among cultures, and the same action has different meanings; thus, when the structure of norms in a culture is identified, the meaning of an action in the culture becomes clear. The research practice of "the Cultural Psychology of Differences" does not aim to create inventories of static differences. When a researcher, who is also a member of a specific culture, witnesses common behavior (cultural practices) among the others belonging to a different culture, the researcher is surprised, and, at the same time, reflects on his or her own common behavior (cultural practices); by doing so, mutual understanding and empathy are deepened, and this is exactly what "the Cultural Psychology of Differences" aims to do. Culture of the others appears dynamically, swaying ourselves; theorizing such a process is the task of our "Cultural Psychology of Differences". We believe this practice of understanding different cultures will provide a practical prescription for mutual understanding through tensions and surprise not only for psychology but also for members of the countries that historically and constantly have had strained relationships. "Cultural Psychology of Differences" is the ideal that cultural psychology to study the relationships between mind and culture should be pursued in the future"--